The Einstein Phenomenon: What Does the New Evidence Say - Krikštopaitis, Juozas Algimantas (Problemos, 2009)
The article presents and analyses a forgotten and perhaps unnoticed book about Einstein, written by David Reichinstein, his contemporary and colleague of studies in Zurich. The book was published in Berlin and Kaunas in 1932. Because of the limited edition and the prevailing political situation, the book became a rarity, eluding the field of view of historians. The book about this great epochal physicist is valuable because it was written by a person who befriended him for several decades. The author reveals a great deal of unique material about Einstein’s worldview, convictions, philosophical deliberations, about his personal character, the political situation, and a merciless critique by leading figures in science. In the article, authentic facts are presented by a direct participant of the events and investigated with an intent to illuminate the intellectual features of Einstein’s activities and the nature of his behaviour while encountering the issues of nationalism and its doctrine. The article is dedicated to commemorate the 130th anniversary of Einstein’s birth.